The role of receptivity in the courtship behavior of Podocnemis erythrocephala in captivity - Ferrara, Camila Rudge; Schneider, Larissa; Vogt, Richard Carl; Burger, Joanna (Acta Ethologica, 2009)
The courtship behavior of Podocnemis erythrocephala (Red-headed Amazon River Turtle) in captivity was studied to examine female receptivity and male response to female rejection. We observed 20 females and 39 males in 150 sessions (3-6 h/day for a total of 450 h). In 36% of the trials, there was no interaction between males and females, and 20% of the trials resulted in copulations. All males introduced into tanks approached females, and eventually there was aggression among the males. In 48% of the experiments, females also searched for or approached males. When males initially approached females, they either accepted the male's advances (14%), rejected the male passively (38%), or rejected the male aggressively (48%). In 86% of the cases where males were rejected, 4% attempted to approach females again, and in 51% they were ultimately successful. © The Author(s) 2009.
Keywords: Dermatemydidae; Podocnemididae; Podocnemis Erythrocephala; Testudines